Building capacities: the next generation of women scientists - Triana Ángel, Natalia; Urrea Benítez, José Luis; Villegas, Daniel Mauricio (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
● From 2015 to 2021, a total of 21 women scientists participated in the LivestockPlus Phase I and II projects. A set of key questions were elaborated to gather the experiences of those women during their time at the Tropical Forages Program. ● Participants identified and narrated several gender gaps in their access to science education, as well as to job opportunities in the same field, even if these gaps were not experienced while they developed their work. ● 25 peer-review journal articles were led by women researchers, playing important roles in achieving scientific publications. Eight women became mothers during their research stay or already were when they joined the projects, which shows the concomitance between maternity and scientific work, although not without certain pitfalls. ● Despite individual and collective efforts to close the gender gap, both in access to educational opportunities and in the labor market, the truth is that women continue to be a minority in the world and scientific praxis. ● Several of the collected testimonies help us understand not only the harm of gender discrimination in STEM, but also the intersectionality that allows, encourages, and exacerbates this gap. ● This experiences are a good example of how inclusive work environments, training opportunities, and promotion of scientific careers bear great fruit, and invite us to redouble our efforts and intentions so that these opportunities continue and improve.